Penguatan Pembelajaran PAI Di Pondok Pesantren Melalui Membaca Kitab Kuning Dengan Metode Amtsilati - Mukhashofatul Imtiyaazah; Asdlori Asdlori (JURNAL ILMIAH NUSANTARA, 2025)
This research aims to describe the strengthening of Islamic Religious Education (PAI) learning at Pondok Pesantren Nurussathi’ Darul Falah Banjarnegara through the study of classical Islamic texts (kitab kuning) using the Amtsilati method. The background of this study lies in the central role of kitab kuning as an authoritative source of Islamic knowledge in pesantren, while many students still face difficulties in understanding unvowelled Arabic texts due to limited mastery of Arabic grammar (nahwu and sharaf). The Amtsilati method emerges as a solution to facilitate students in learning kitab kuning in a more practical and applicative way.This research employs a qualitative descriptive approach with field research design. Data were collected through interviews, observation, and documentation, then analyzed comprehensively to describe the implementation process, supporting and inhibiting factors, as well as the impacts of the Amtsilati method.The findings reveal that the implementation of PAI learning through kitab kuning with the Amtsilati method is conducted systematically and structurally. The method has proven effective in helping students understand grammatical rules and improve their ability to read classical texts. Furthermore, the use of Amtsilati positively impacts students’ academic performance, learning independence, as well as their spiritual and moral development. Supporting factors include the active role of teachers, students’ motivation, and a well-structured schedule, while inhibiting factors mainly come from differences in students’ background knowledge and limited facilities.